Molecular Targets for Combined Therapeutic Strategies to Limit Glioblastoma Cell Migration and Invasion - Yool, Andrea J.; Ramesh, Sunita (Frontiers in Pharmacology, 2020)
The highly invasive nature of glioblastoma imposes poor prospects for patient survival. Molecular evidence indicates glioblastoma cells undergo an intriguing expansion of phenotypic properties to include neuron-like signaling using excitable membrane ion channels and synaptic proteins, augmenting survival and motility. Neurotransmitter receptors, membrane signaling, excitatory receptors, and Ca2+ responses are important candidates for the design of customized treatments for cancers within the heterogeneous central nervous system. Relatively few published studies of glioblastoma multiforme (GBM) have evaluated pharmacological agents targeted to sigaling pathways in limiting cancer cell motility. Transcriptomic analyses here identified classes of ion channels, ionotropic receptors, and synaptic proteins that are enriched in human glioblastoma biopsy samples. The pattern of GBM-enriched gene expression points to a major role for glutamate signaling. However, the predominant role of AMPA receptors in fast excitatory signaling throughout the central nervous system raises a challenge on how to target inhibitors selectively to cancer cells while maintaining tolerability. This review critically evaluates a panel of ligand- and voltage-gated ion channels and synaptic proteins upregulated in GBM, and the evidence for their potential roles in the pathological disease progress. Evidence suggests combinations of therapies could be more effective than single agents alone. Natural plant products used in traditional medicines for the treatment of glioblastoma contain flavonoids, terpenoids, polyphenols, epigallocatechin gallate, quinones and saponins which might serendipitously include agents that modulate some classes of signaling compounds highlighted in this review. New therapeutic strategies are likely to exploit evidence-based combinations of selected agents, each at a low dose, to create new cancer cell-specific therapeutics.